Defining children who may have palliative care needs: a delphi consensus building study. (4th April 2011) - Brook, L A; Kerr, C; Hawker, S
Abstract : Background: Attempts to identify children who may have palliative care needs using standard ACT definitions identified ambiguity and differences in interpretation. A Delphi study developed definitions that would be acceptable to healthcare professionals and define children who may have palliative care needs to facilitate collection of a minimum dataset. Methods: Two Delphi survey rounds, completed by 44 professionals with expertise in paediatric palliative care, were followed by a Delphi consensus building one-day conference involving 13 participants. The standard definition of palliative care for children was not changed. Professionals rated their level of agreement with proposed interpretation of standard definitions of life threatening and life limiting conditions or suggested alternative. Areas of difference and proposed alternative interpretations were explored in the Delphi workshop. Results: Consensus was for diagnosis/recognition and onset before the 18th birthday. Interpretation of definitions varied with respondent type. Thematic analysis revealed five key themes: ▶ Life expectancy in the context of children's palliative care ▶ Conditions that carry a risk of mortality ▶ Access to services and the transition to adult care ▶ Consistency ▶ Quantifying hope Using prognosis to identify children with palliative care needs was felt to be inappropriate as prognostication is often inaccurate and professionals maybe reluctant to give a poor prognosis or identify children as 'palliative'. ACT groups provide a useful descriptor of the child's anticipated journey but the ACT group may change as the child's condition progresses. ACT groups only identify possible palliative care needs when applied to a cohort of children who are currently living. The use of the 'surprise question' was proposed as the most appropriate method of identifying children who may have palliative care needs. Professionals were more comfortable with the uncertainty implicit in 'not being surprised' if a child died rather than 'expecting' a child to die. A 'Rainbow of children's palliative care needs' in conjunction with a range of 'surprise questions' was proposed to describe different groups of children who may have palliative care needs. Conclusions: Consensus definitions of children with palliative care needs are essential to facilitate standardised collection of a children's palliative care minimum dataset.